Post-Basic Education and Training in Rwanda : Skills Development for Dynamic Economic Growth - World Bank (Washington, DC, 2013)
Improved access to and quality of upper secondary schools, teacher training colleges, Higher Learning Institutions (HLIs), and demand-driven Technical and Vocational Education and Training (TVET) courses to supply the demand for the higher-level skills and competencies relevant to labor market needs remains a central priority for the ministry of education in Rwanda. Since the original analysis and drafting of this report took place there have been a number of changes within the Post Basic Education and Training (PBET) sector and progress has been made on various areas of policy implementation discussed in the report. Most significantly, the government of Rwanda announced in 2010 that all students will be entitled to access fee-free education until the end of upper secondary school (or equivalent). This policy move addresses some of the concerns raised in the report to ensure that increasing numbers of basic education graduates can move on to PBET. This report provides a description of key aspects of the education sector as a whole with particular emphasis on quality improvement in basic education. The present report takes the perspective that Rwanda's PBET system is the country's principle mechanism for generating the skilled labor force needed to become a middle-income, knowledge- and expert-based economy. PBET in this report is defined as all formal education and training for which the entry requirement is the completion of at least basic education. This report is structured as follows: chapter one describes Rwanda's recent growth trends, ambitions for the future, and the role that skills development must play to ensure that these ambitions can be reached. Chapter two shows an analysis of the Rwandan labor market, exploring trends in both labor supply and demand, with an emphasis on the educational attainment of the labor force. Chapter three describes the context of PBET policies and strategies and the structure of the PBET system, highlighting the key features of its various segments. Chapter four focuses on the governance, management, and financing of the PBET system. Chapter five builds on the preceding chapters to offer a set of policy options that, when implemented, are expected to contribute to the promotion of a well-integrated and managed system.